ANALISIS FAIRNESS DAN INCENTIVE CONTRACTING PADA KINERJA BERBASIS ANGGARAN ATAS PENGUJIAN: EKSPERIMEN (STUDI KASUS PADA MAHASISWA PASCASARJANA DIUNIVERSITAS MALIKUSSALEH TANUN 2017- 2018) - Hendra Raza; Cut Fauziah (Jurnal Akuntansi dan Keuangan, 2018)
This study aimed to determine the analysis of fairness and incentive contracting on performance-based budget testing experiments. The data used in this research were primary data. The population in this study consisted of 59 postgraduate students who were on Lancang Garam St, postgraduate campus of Malikussaleh University with an observation period starting from 2017-2018. The sampling method was purposive sampling. The number of samples that meet the research criteria based on existing considerations was that all postgraduate students management in science during 2017-2018 as many as 59 respondents. The method used to analyze the relationship between independent variables and the dependent variable was Multiple linear regression analysis and Classical assumption test. The test results showed that the planning variable was accepted because the value was significantly higher, namely the difference between fairness and budget-based performance, while the other side is accepted also because it was seen from a significantly higher value that was with the difference between fairness towards the budget process, which has been studied from 59 students on the postgraduate campus of Malikussaleh University.